Insights from in vivo preclinical cancer studies with histotripsy - Tejaswi Worlikar; Timothy Hall; Man Zhang; Mishal Mendiratta-Lala; Michael Green; Clifford S. Cho; Zhen Xu (International Journal of Hyperthermia)
Histotripsy is the first noninvasive, non-ionizing, and non-thermal ablation technique that mechanically fractionates target tissue into acellular homogenate via controlled acoustic cavitation. Histotripsy has been evaluated for various preclinical applications requiring noninvasive tissue removal including cancer, brain surgery, blood clot and hematoma liquefaction, and correction of neonatal congenital heart defects. Promising preclinical results including local tumor suppression, improved survival outcomes, local and systemic anti-tumor immune responses, and histotripsy-induced abscopal effects have been reported in various animal tumor models. Histotripsy is also being investigated in veterinary patients with spontaneously arising tumors. Research is underway to combine histotripsy with immunotherapy and chemotherapy to improve therapeutic outcomes. In addition to preclinical cancer research, human clinical trials are ongoing for the treatment of liver tumors and renal tumors. Histotripsy has been recently approved by the FDA for noninvasive treatment of liver tumors. This review highlights key learnings from in vivo shock-scattering histotripsy, intrinsic threshold histotripsy, and boiling histotripsy cancer studies treating cancers of different anatomic locations and discusses the major considerations in planning in vivo histotripsy studies regarding instrumentation, tumor model, study design, treatment dose, and post-treatment tumor monitoring.